The Human Right to Decent Housing and the Possibilities of Access to Justice for its Protection in Favor of Vulnerable Sectors - Huancapaza Hilasaca, Joel Emerson (2024)
The best criterion to understand the importance of the right to adequate housing or decent housing is its legal foundations. The problem is that a lot of ink has been spilled by lawyers and judges without distinguishing that when it comes to human rights such as decent housing, there are two types of foundations: visible foundations and invisible foundations. The first has to do with the international and national regulatory framework; while the latter have to do with the moral weight that said regulatory framework has. In the present work, the visible foundations are preeminently exposed, and a preliminary outline of the invisible foundations is left.